pencegahan hipotermi pada bayi ny. S dengan bblrdi RSUD Pandan Arang Boyolali - Riadinata, Eryan, Siti Arifah, S.Kp., M.Kes (2016)
Infants with low birth weight (LBW) becomes a risk factor that can lead to increased morbidity and infant mortality. Many issues can occur in infants with low birth weight as a risk of infection, difficulty breathing, hypothermia, sucking reflex is lacking, nutritional disorders, hypoglycemia, intracranial hemorrhage, meconium aspiration syndrome, and hyperbilirubinemia. Hypothermia is a sign of danger because it can cause changes in the body's metabolism, hypoglycemia, metabolic acidosis, shortness of breath. According Riskesdas (2013) prevalence of LBW in Boyolali by 6.6%. The general objective of writing a scientific paper is to find ways to prevent hypothermia in infants with low birth weight in accordance with the standards of nursing. Special-purpose writing scientific papers are conducting studies, data analysis, formulate nursing diagnoses, also prepared a plan of action, nursing action in accordance with the action plan, and evaluate nursing actions for the prevention of hypothermia on LBW. Results: After nursing action for 3 x 24 hours the risk of hypothermia in infants resolved. Conclusions: Efforts to prevent the risk of hypothermia done to By. Ny. S using nursing care in accordance with the standards of nursing for three days, then showed that on By. Ny. S hypothermia has been resolved and within normal limits.